Mitigation for Hawser‘s Short Fatigue Life on The Study of The Fatigue Life Prediction of Hawser in Single Point Mooring (SPM) at Tuban Fuel Terminal - Ahmad Syafiul Mujahid (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2019)
One of the vital components of SPM System is Mooring Hawser. Mooring Hawser is mooring lines that used to anchor the tanker ship that are berthed at Single Point Mooring (SPM) fuel terminal to loading or offloading the fuel oil. The incident of broken hawser unexpectedly due to short fatigue life that occurs on hawser when tanker ship that is anchored at SPM 150.000 DWT at Tuban Seas, East Java, Indonesia is the basis of this study for mitigation and replace of new hawser. This study calculates fatigue life of the hawser by using numerical simulation approach and Palmgren-Miner Methods. the hawser variation that conducted is only at the size of the outside diameter, namely: 0.144 m, 0.152 m, and 0.160 m. The material properties of the hawser in this study are Nylon Polyamide PA66. Numerical simulation consist of two steps: Hydrodynamics diffraction numerical simulation is used to obtain response (RAO) of tanker ship and SPM, and hydrodynamics time response numerical simulation is used to obtain effective hawser tension time history in 3600 second time simulation. By using the S-N Curve of Nylon Polyamide PA66 that is obtained from Jernej Klemenc, Andrej Wagner, and Matija Fadjiga (2011) as the basis to calculate fatigue life prediction of three variations in the outside diameter of the hawserwith Palmgren-Miner methods. The calculation result of new hawser fatigue life = 57.40536 Months or 4.718249 Years of Effective Berthing Time. The new hawser use outside diameter variation = 0.152 m to replace the previous hawser.